RELIGIOUN-BASED COUNSELING GUIDANCE SERVICES ON STUDENT MORALS - Aditya Adiyansa Kiwang; Iceu Susana, Siti Nurmala, Novi Ardilah (International Journal of Teaching and Learning, 2024)
The purpose of this study is to describe the implementation of the counseling guidance approach to student behavior in the classroom. This research uses a qualitative descriptive method by collecting data based on factual information, where the data is in the form of readable text that can be analyzed. The conclusion that can be drawn from this research is that teachers who teach counseling guidance have a very important role in the development of student morals in the classroom, specifically teachers as educators act as role models and examples that students will follow. In addition, religious-based counseling guidance is provided to students in a thoughtful way through various methods, including discussions, interviews, and private teachers.